Severe Encephalatrophy and Related Disorders From Long-Term Ketamine Abuse: A Case Report and Literature Review - Liu, Linying; Huang, Haijian; Li, Yongbin; Zhang, Ruochen; Wei, Yongbao; Wu, Weiwei (Frontiers in Psychiatry, 2021)
Ketamine is a glutamate N-methyl D-aspartate receptor antagonist and an anaesthetic agent that has been effectively used to treat depression. However, ketamine has also been increasingly used for recreational purposes. The dissociative side-effects of ketamine use, such as hallucinations, are the reason for abuse. Additionally, long-term ketamine abuse has been highly associated with liver-gallbladder and urinary symptoms. The present study reports the case of a 28-year-old young male adult with an 8-year history of daily inhalation of ketamine. We investigated the association between ketamine abuse and the mechanism of its adverse effects, particularly encephalatrophy, and attempted to find a link between these disorders. These results would help us to better understand ketamine usage, ketamine abuse effects and the addictive mechanism. To the best of our knowledge, the present case is the first report of severe brain atrophy related to ketamine abuse. Details of the patient are presented and the mechanism of the encephalatropy-associated ketamine abuse is discussed. Furthermore, organ dysfunction following chronic ketamine abuse may indicate that the side effects are the result of comprehensive action on multiple regions in the brain.